Motivasi Mahasiswa Penjaskesrek UNP Kediri dalam Kegiatan Mendaki Gunung - Dian Indah Nur Soffi; Puspodari; Dhedhy Yuliawan (Universitas Mercu Buana Yogyakarta, 2026)
Mountain hiking is one of the most popular forms of outdoor recreational sports among university students, particularly those enrolled in the Physical Education, Health, and Recreation Study Program. This activity provides not only physical benefits but also psychological, social, and personal development benefits. This study aimed to explore the motivations of students in the Physical Education, Health, and Recreation Study Program at Universitas Nusantara PGRI Kediri to participate in mountain hiking activities. This research employed a qualitative approach with a phenomenological design. Seven students who had participated in mountain hiking more than once were selected using purposive sampling. Data were collected through in-depth interviews conducted between March and June 2026, supplemented by documentation. Data trustworthiness was ensured through source triangulation and member checking. Data were analyzed using the Miles, Huberman, and Saldaña interactive analysis model. The findings revealed that students' motivations were both extrinsic and intrinsic. Extrinsic motivation included influences from friends, social media, and social relationships. In contrast, intrinsic motivation encompasses a love of nature, personal satisfaction, psychological benefits, physical health benefits, and challenges for personal growth. The findings indicate that intrinsic motivation is the primary factor sustaining students' participation in mountain hiking activities. entitled to continue engaging in mountain climbing activities.